Melatonin expression in periodontitis and obesity: An experimental in‐vivo investigation. (14th June 2018) - Virto, L.; Haugen, H. J.; Fernández‐Mateos, P.; Cano, P.; González, J.; Jiménez‐Ortega, V.; Esquifino, A. I.; Sanz, M.
Abstract : Background and Objective: Melatonin deficiency has been associated with obesity and systemic inflammation. This study aims to evaluate whether melatonin could interfere with the mechanisms of co‐morbidity linking obesity and periodontitis. Material and Methods: Twenty‐eight male Wistar rats were randomly divided in 4 groups: control group (Con) (fed with standard diet); high‐fat diet group (HFD) (fed with a diet containing 35.2% fat); Con group with induced periodontitis (Con‐Perio) and HFD group with induced periodontitis (HFD‐Perio). To induce periodontitis, the method of oral gavages with Porphyromonas gingivalis ATCC W83K1 and Fusobacterium nucleatum DMSZ 20482 was used. Circulating melatonin levels were analyzed by multiplex immunoassays. Periodontitis was assessed by alveolar bone loss (micro‐computed tomography and histology) and by surrogate inflammatory outcomes (periodontal pocket depth, modified gingival index and plaque dental index). Results: Plasma melatonin levels were significantly decreased ( P  < .05) in the obese rats with periodontitis when compared with controls or with either obese or periodontitis rats. Alveolar bone loss increased 27.71% (2.28 µm) in HFD‐Perio group compared with the Con group. The histological analysis showed marked periodontal tissue destruction with osteoclast activity, particularly in the HFD‐Perio group. A significant negative correlation ( P  < .05) was found between periodontal pocket depth, modified gingival index and circulating melatonin levels. Conclusion: Obese and periodontitis demonstrated significantly lower melatonin concentrations when compared with controls, but in obese rats with periodontitis these concentrations were even significantly lower when compared with either periodontitis or obese rats. These results may indicate that melatonin deficiency could be a key mechanism explaining the co‐morbidity effect in the association between obesity and periodontitis.